Exploring the Components of Digital Identity on Social Networks Sites: Identifier, Post, Profile Photo, and Selfie - Reda, El Yazidi (European Scientific Journal, ESJ, 2024)
The digital age has ushered in a paradigm shift in self-expression and identity construction, with social network sites (SNSs) serving as vibrant canvases for individuals to shape and project their digital personality. This paper focuses on delving into the intricate components of digital identity on SNS, focusing on four key elements: identifiers, posts, profile photos, and selfies. Based on a descriptive and analytical method, this article attempts to draw up a detailed and nuanced analysis of the multiple facets of digital identity, thus providing a solid basis for in-depth understanding of this complex phenomenon in the specific context of social networks which technically regulate the representation of self. The results obtained show that the construction of a digital identity is framed by the architecture of SNSs, which incite users to manifest their selves, thus producing unlimited digital traces that reflect their personality traits. The results also provide an understanding of the structure of SNSs that aim to raise awareness of presenting a positive self-image in the digital world.